2002
DOI: 10.1111/1467-839x.00101
|View full text |Cite
|
Sign up to set email alerts
|

Self‐enhancement in Japan and America

Abstract: North Americans view themselves in more positive terms than they view most other people. In the present paper, we report three studies showing that this bias is also found in Japan. For highly valued traits and abilities, Japanese students rated themselves and their best friends in more positive terms than they rated most other students (Study 1 and Study 2) and most other Japanese (Study 2). In Study 3, a sample of older Japanese displayed the same tendency when evaluating themselves and a member of their fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
168
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 58 publications
11
168
2
Order By: Relevance
“…This result also contrasts with the cultural moderation reported by Endo et al (2000) and Brown and Kobayashi (2002), who found that Japanese participants provided lower positive ratings of themselves, their relationships, and the generalized other than did North American respondents. This opens the interesting possibility that the form that cultural moderation takes may vary across cultures.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This result also contrasts with the cultural moderation reported by Endo et al (2000) and Brown and Kobayashi (2002), who found that Japanese participants provided lower positive ratings of themselves, their relationships, and the generalized other than did North American respondents. This opens the interesting possibility that the form that cultural moderation takes may vary across cultures.…”
Section: Discussioncontrasting
confidence: 97%
“…There is also an emerging literature comparing these illusions among North American and Asian populations. Although self-enhancement and relationship enhancement biases have been documented in Japanese (Brown & Kobayashi, 2002;Heine & Renshaw, 2002), Chinese (Falbo et al, 1997), Israeli, and Singaporean samples (Kurman & Sriram, 1997), the biases tend to be less pronounced in the Asian samples than in American samples. Our results add to this literature by indicating that cultural group moderates the extent of positive illusions when comparing U.S. and Turkish samples of individuals in consanguineous and nonconsanguineous marriages as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that East Asians are willing to show intergroup attributional bias even though they do not always exhibit self-serving attributional bias at individual level (e.g., Brown & Kobayashi, 2002;Ma, 2003;Muramoto & Yamaguchi, 1997; but see also Heine, 2003). Empirical support for this contention, however, has not been sufficient especially in research referring to Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…Data from cross-cultural studies have also supported this idea. For example, in one series of studies, Japanese were found to self-enhance on culturally important traits (Brown & Kobayashi, 2002;2003) and these findings were replicated and extended in another series of studies where Japanese were found to selfenhance on collectivistic traits, but not on individualistic traits (Sedikides, Gaertner, & Toguchi, 2003). For a summary, including meta-analyses, of evidence for both sides of the debate on universal self-enhancement see Heine (2005), and Heine, Kitayama, & Hamamura (2007) and Sedikides, Gaertner, & Vevea (2005).…”
mentioning
confidence: 91%